2021
DOI: 10.1785/0120200326
|View full text |Cite
|
Sign up to set email alerts
|

Canonical Correlation Analysis Based on Site-Response Proxies to Predict Site-Specific Amplification Functions in Switzerland

Abstract: The national seismic networks of Switzerland comprise more than 200 stations. At the station sites, the empirical amplification functions (EAFs) are routinely computed after each earthquake using a generalized inversion method based on separation of source, path, and site effects. The seismic stations are also characterized through geophysical measurements aiming to estimate shear-wave velocity profiles and horizontal-to-vertical spectral ratio of ambient vibrations (HVNR). Using this information, the correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 42 publications
3
32
0
Order By: Relevance
“…The reason is probably the dominance of the artificial fillings (Figure 2B) that increases the variability of the site response and due to higher density of the infrastructure in the city center affecting the ambient noise wavefield. In the future, we would also apply other methods such as canonical correlations (Panzera et al, 2021) or simulations of wave propagation using numerical modeling that may help us to validate the model.…”
Section: Amplification Map For the Lucerne Areamentioning
confidence: 99%
“…The reason is probably the dominance of the artificial fillings (Figure 2B) that increases the variability of the site response and due to higher density of the infrastructure in the city center affecting the ambient noise wavefield. In the future, we would also apply other methods such as canonical correlations (Panzera et al, 2021) or simulations of wave propagation using numerical modeling that may help us to validate the model.…”
Section: Amplification Map For the Lucerne Areamentioning
confidence: 99%
“…In this study, the two sets of variables are the HVSRc and amplification functions (AF), both on a logarithmic scale, discretized within 16 frequency bins in the range of 0.50-10.00 Hz (Figures 4, 6). The bin subdivision used in this study is the same as in Panzera et al (2021), who demonstrated that 16 bins are sufficient to preserve as much as possible of the HVSRc and AF fluctuations in amplitude. The average amplitude Am(k) within the kth bin is computed as a weighted mean,…”
Section: Canonical Correlationmentioning
confidence: 99%
“…To reconstruct the amplification from HVSRc, we used the approach proposed by Panzera et al (2021). The method consists of solving the inverse problem for Eq.…”
Section: Canonical Correlationmentioning
confidence: 99%
See 2 more Smart Citations